Mechanically Robust Polyurethane Microfibrous Membranes Exhibiting High Air Permeability (Journal of Fiber Bioengineering and Informatics, 2012)
Microporous polyurethane (PU) nano-microfibrous membranes exhibiting robust mechanical propertywith high air permeability were prepared using one-step electrospinning method. The role of compositionsof electrospinning solution on the morphology, hydrophobicity and mechanical property of PU membraneswere discussed, and a probable two-step break mechanism upon the external stress is proposed.Furthermore, the as-prepared membranes exhibited good air permeability (5.9 mm/s), high waterresistance (5.7 kPa), and water vapor transmittance (7868 g/m², 24 h), and comparable tensile strength(15.95 MPa), suggesting their use as promising materials for various potential applications in protectiveclothing, membrane distillation, bioseparation, tissue engineering and catalyst carriers, etc.